Linguistic Means of Reflecting Social Differences in British Press - V. V. Ignatenko (Vestnik MGIMO-Universiteta)
The article deals with the main tendencies of modern British newspaper language addressed to readers with different background. Comparing texts in «quality» newspapers and «middlebrow» tabloids allows to reveal linguistic means differing according to social audiences.